2012
DOI: 10.1093/her/cys079
|View full text |Cite
|
Sign up to set email alerts
|

The effect of participatory community-based diabetes cares on the control of diabetes and its risk factors in western suburb of Yasouj, Iran

Abstract: This study aimed to investigate whether a community-based participatory diabetes care program could efficiently improve diabetic care and reduce its risk factors. To induce a participatory approach, a local group was established in partnership with academics, local leaders, health providers and public representatives. The group conducted community needs assessment and priority setting process. Diabetes was identified as the first priority health problem in this area. A total of 2569 30- to 65-year-old resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…28,30,33 Of the 14 studies measuring A1C, 9 demonstrated statistically significant reduction in A1C. 29,31,33,[37][38][39][40][41][42] Of the 9 studies measuring BP, 3 demonstrated statistically significant improvements in BP. 27,38,41 Three of the 6 studies measuring lipids demonstrated statistically significant improvements in lipids, 30,40,42 and 4 of the 5 studies measuring fasting glucose demonstrated statistically significant improvements in fasting glucose.…”
Section: Study Characteristics and Outcomes Of Studiesmentioning
confidence: 98%
See 4 more Smart Citations
“…28,30,33 Of the 14 studies measuring A1C, 9 demonstrated statistically significant reduction in A1C. 29,31,33,[37][38][39][40][41][42] Of the 9 studies measuring BP, 3 demonstrated statistically significant improvements in BP. 27,38,41 Three of the 6 studies measuring lipids demonstrated statistically significant improvements in lipids, 30,40,42 and 4 of the 5 studies measuring fasting glucose demonstrated statistically significant improvements in fasting glucose.…”
Section: Study Characteristics and Outcomes Of Studiesmentioning
confidence: 98%
“…[28][29][30][31][32][33][34][35][36][38][39][40] Four studies were conducted outside the US in the following countries: Belgium, 37 Dominican Republic, 41 India, 27 and Iran. 42 When looking at each study by community setting, 11 studies were conducted in a local community site, 28,30,31,[33][34][35]38,[40][41][42] 1 study was conducted in a community pharmacy, 37 2 studies were conducted at a community clinic, 29,32 and 2 studies were conducted in the home or a community site based on participant availability. 36,39 Additionally, Table 1 summarizes the type of intervention that was conducted as well as the impact on outcomes.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations